Synergistic effect of hydrophilic polyglycerol fatty acid esters and protein on the stability of interfacial membrane in low-fat aerated emulsions with different homogenization conditions - Han, Wanjun; Chai, Xiuhang; Sun, Yanwen; Tan, Chin Ping; Liu, Yuanfa (Elsevier BV, 2023)
This study investigates the impact of various chain lengths of hydrophilic polyglycerol fatty acid esters (HPGEs), namely SWA-10D, M-7D and M-10D on protein interactions and their influence on the surface morphology and interfacial properties of low-fat aerated emulsions under different pressures conditions. M-7D and M-10D samples exhibited larger particle sizes, higher ζ-potential and rougher surface compared to SWA-10D sample at 1 % concentration of HPGEs. Consequently, M-7D and M-10D samples demonstrated lower values of G′, G′′, and higher values tan δ at the oil–water interface as pressure increased, thereby promoting the formation of less viscoelastic structures. M-7D sample, characterized by lower content of α-helix structures, resulted in an observable redshift in the N[sbnd]H and C[dbnd]O groups of the protein. Molecular docking analysis affirmed that M-7D sample exhibited a lower absolute binding energy value, indicating stronger interaction with the protein compared to other samples, ultimately contributing to the unstable interfacial membrane formed.